KEBERADAAN TUHA PEUT GAMPONG DALAM PENYELESAIANPERSELISIHAN HUKUM ADAT ACEH - Apri Rotin Djusfi (Jurnal Public Policy, 2016)
Based on Pasal 18 Paragraph (2) of 1945 Constitution states that "the government of province and district / city set up and manages their own affairs in accordance with the principle of autonomy and duty of assistance". Then it was mentioned in Article 18B Paragraph (1) and Paragraph (2) which states that the State shall recognize and respect the units of local government which is special and privileged, and respect the customary law community unit along with their traditional rights.Tuha Peut institution is one of the traditional institutions in Acehnese society which has the authority to maintain the existence of customary law for generations. Constituent on the Governing of Aceh mandates that the resolution of social problems customarily taken through traditional institutions. Whereas, traditional institutions have function and act as a vehicle for public participation in the implementation of the Aceh Government and district / city governments in the field of peacefullness, tranquility, harmony, and public order. Keywords: Tuha Peut, Traditional Institutions.